Zygomatic bone: Anatomic bases for osseointegrated implant anchorage - Rigolizzo, Maurício Bruhns; Camilli, José Angelo; Francischone, Carlos Eduardo; Padovani, Carlos Roberto [UNESP]; Brånemark, Per-Ingvar (My University, 2005)
Purpose: The aim of the present study was to evaluate zygomatic bone thickness considering a possible relationship between this parameter and cephalic index (Cl) for better use of Cl in the implant placement technique. Materials and Methods: Cl was calculated for 60 dry Brazilian skulls. The zygo matic bones of the skulls were divided into 13 standardized sections for measurement. Bilateral measurements of zygomatic bone thickness were made on dry skulls. Results: Sections 5, 6, 8, and 9 were appropriate for implant anchorage in terms of location. The mean thicknesses of these sections were 6.05 mm for section 5, 3.15 mm for section 6, 6.13 mm for section 8, and 4.75 mm for section 9. In only 1 section, section 8, did mean thickness on 1 side of of the skull differ significantly from mean thickness on the other side (P <.001). Discussion: For the relationship between quadrant thick ness and Cl, sections 6 and 8 varied independently of Cl. Section 5 associated with brachycephaly, and section 9 associated with subbrachycephaly, presented variations in the corresponding thickness. Conclusion: Based on the results, implants should be placed in sections 5 and 8, since they presented the greatest thickness, except in brachycephalic subjects, where thickness was greatest in section 5, and in subbrachycephalic subjects, where thickness was greatest in section 9. Cl did not prove to be an appropriate parameter for evaluating zygomatic bone thickness for this sampling.
Keywords: Atrophic maxilla; Cephalic index; Dental implants; Zygomatic bone; adolescent; adult; aged; bone regeneration; brachycephaly; Brazil; calculation; cephalometry; controlled study; craniofacial synostosis; female; histology; human; human tissue; male; maxilla; methodology; parameter; pathology; scoring system; skull; standardization; statistical significance; thickness; tooth implantation; zygoma; Adolescent; Adult; Aged; Aged, 80 and over; Cephalometry; Craniosynostoses; Dental Implantation, Endosseous; Dental Implants; Female; Humans; Male; Middle Aged; Osseointegration; Skull; Zygoma